2011
DOI: 10.1080/10934529.2011.542386
|View full text |Cite
|
Sign up to set email alerts
|

Survival of infectious prions in Class B biosolids

Abstract: This study developed a method for extracting infectious prions from Class B biosolids and subsequently evaluated the survival of infectious prions under the influence of mesophilic (37°C) and thermophilic (60°C) temperatures in Class B biosolids. Unlike other studies, this study utilized a scrapie cell assay to determine infectivity and quantity of infectious prions. The best method for extraction was exposing the biosolids to 4 M urea at 80°C for 10 minutes followed by a membrane centrifugation to reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…First, the mobility of prions is limited in environmental samples such as soil and waste materials, including composted yard waste and municipal solid waste . The detachment of PrP TSE from these environmental samples has not been observed even under stringent chaotropic agents, nonionic detergents, or extreme pH. , Furthermore, PrP TSE remains attached to stainless steel surgical instruments and can cause infection even after extensive decontamination, including sonication, chemical reagents, enzymatic disinfectants, and steam autoclaving at 134 °C . The possible migration of PrP TSE in our lab-scale compost was analyzed by WB, but no PrP TSE signals were detected in compost samples collected within the vicinity of nylon bags.…”
Section: Discussionmentioning
confidence: 99%
“…First, the mobility of prions is limited in environmental samples such as soil and waste materials, including composted yard waste and municipal solid waste . The detachment of PrP TSE from these environmental samples has not been observed even under stringent chaotropic agents, nonionic detergents, or extreme pH. , Furthermore, PrP TSE remains attached to stainless steel surgical instruments and can cause infection even after extensive decontamination, including sonication, chemical reagents, enzymatic disinfectants, and steam autoclaving at 134 °C . The possible migration of PrP TSE in our lab-scale compost was analyzed by WB, but no PrP TSE signals were detected in compost samples collected within the vicinity of nylon bags.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the mobility of prions is limited in environmental samples such as soil 7,53 , composted yard waste and municipal solid waste 54 . The mobility of PrP TSE in these environmental samples was not observed even after exposure to stringent chaotropic agents, nonionic detergents or extreme pH 55,56 . These observations suggest that during composting, the mobility of PrP BSE from manure spheres or their cleavage from stainless steel wires was unlikely.…”
Section: Discussionmentioning
confidence: 84%
“…Mouse‐adapted scrapie cell line assay have also been used to evaluate the survival of prions in sewage, with a reduction of infectivity of 0·5 log when incubated at 25°C in wastewater for 1 week, a 2·43 log reduction after anaerobic digestion in sewage sludge at 37°C for 15 days and a 3·41 log reduction when the temperature was increased to 60°C for 10 days (Miles et al . ,b). However, concern has been expressed with these results as to whether the cell line assay was affected by the biosolids matrix (Booth et al .…”
Section: Methodsmentioning
confidence: 99%